2010
DOI: 10.2478/s11535-010-0090-5
|View full text |Cite
|
Sign up to set email alerts
|

Reducing power and radical scavenging activity of four Parmeliaceae species

Abstract: Abstract:The methanol extracts of four Parmeliaceae lichens (Hypogymnia physodes, Evernia prunastri, Flavoparmelia caperata and Parmelia sulcata) were screened for antioxidant properties and total phenol content. The H. physodes extract was the most effective at reducing iron(III) and scavenging 1,1-diphenyl-2-picrylhydrazyl radicals, while the P. sulcata extract was the most effective in reducing molybdenum(VI) in an acidic medium. The E. prunastri and H. physodes extracts contained more Folin-Ciocalteu reage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 22 publications
2
23
2
1
Order By: Relevance
“…Thus, the biological properties of extract from the thalli of H. physodes grown in Poland may differ from those of H. physodes in other countries, where the lichen may be exposed to other environmental factors. According to the results of the present study, the antioxidant activity of the acetone extract from H. physodes was two to three times higher than that reported for methanolic extract in previous studies (Stojanović et al 2010;Mitrović et al 2011). The strong antioxidant activity may be attributed to its high content of polyphenols.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Thus, the biological properties of extract from the thalli of H. physodes grown in Poland may differ from those of H. physodes in other countries, where the lichen may be exposed to other environmental factors. According to the results of the present study, the antioxidant activity of the acetone extract from H. physodes was two to three times higher than that reported for methanolic extract in previous studies (Stojanović et al 2010;Mitrović et al 2011). The strong antioxidant activity may be attributed to its high content of polyphenols.…”
Section: Discussioncontrasting
confidence: 58%
“…A few studies have investigated the antioxidant properties of extracts obtained from H. physodes. For example, Mitrović et al (2011) and Stojanović et al (2010) reported the IC 50 values for methanolic extracts (45.57 lg/mL and 79.70 lg/mL), and reported the percentage of inhibition of DPPH radicals by methanolic (73.18%), acetone (60.18%) and aqueous (30.98%) extracts from H. physodes. Climatic conditions, such as high light intensity, high temperature and air pollution, have been shown to play important roles in the production of lichen metabolites and to influence their biological properties (Bartak et al 2004;Weissman et al 2006;Millot et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Some lichen extracts and metabolites have already been reported for antioxidant properties due to their phenolic content; for instance, the antioxidant activities of some depsides and depsidones isolated from several lichen species have been demonstrated (de Paz et al, 2010;Hidalgo et al, 1994;Jayaprakasha & Rao, 2000), as well as the in vitro properties of some lichen extracts (Gülçin et al, 2002;Stojanović et al, 2010). Even so, both studies on intracellular ROS modulation by lichen metabolites/extracts and their in vivo effects have been recently started.…”
Section: Antioxidant Properties Of Lichensmentioning
confidence: 99%
“…The DPPH assay was performed as previously described [24]. Radical scavenging activity (RSC) of the essential oils was calculated applying following equation: DPPH RSC(%)=100 (A 0 −A 1 /A 0 ) Where: A 0 -absorbance of the blank; A 1 -absorbance of the sample.…”
Section: 1-diphenyl-2-picrylhydrasyl (Dpph) Radical Scavenging Assaymentioning
confidence: 99%
“…Reducing power of the oils was determined as described previously [24] and expressed in relation to the reducing power of ascorbic acid as a positive control (Ascorbate Equivalent Antioxidant Capacity).…”
Section: Total Reducing Power Assay Fe(iii) To Fe(ii)mentioning
confidence: 99%